Improving Students’ Vocabulary and Activeness Using Mind Mapping: A Classroom Action Research of 1st Semester Students of Law Faculty Semarang University - Stefani Dewi Rosaria; Devy Angga Gunantar; Hetty Catur Ellyawati (ETERNAL (English Teaching Journal), 2019)
The objective of this research is to improve students’ vocabulary and activity during teaching-learning process using mind mapping as a teaching method. This is a classroom action research conducted at Semarang University and the sample is taken from the first semester students of law faculty. This classroom action research applies two cycles. Each cycle includes planning, acting, observing and reflecting. The result showed that through mind mapping students can master English vocabulary easily especially English vocabulary for law, their test score improved, and they became active enough in participating in class such as asking and answering question, delivering opinion, and completing task.